Konsep Pengorganisasian (Organizing) Pendidikan Agama Islam pada SMA Negeri 6 Palembang - Leny Marlina; Mursyidah Mursyidah (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
Palembang Public Senior High School 6 is a high school with the predicate of IMTAQ and Religious from the Government. Being a superior school must be supported by good management, including organizing. These advantages encourage researchers to analyze in depth how the organizing (organizing) the inputs, processes, outputs and outcomes of Islamic religious education in schools. Type of case study research is qualitative with inductive thinking logic and intrinsic case study research type. Organizational activities (organizing) mostly carried out, although there are still teachers too late preparing the learning tools. The research findings found that in addition to organizing input, process, output and outcome activities, there is continuity of the program and regeneration. The religious program is presented, held in stages and continuously starts until graduation and from the time you come home. Kaderisasi was built by utilizing alumni (wasilah) from SMA Negeri 6 Palembang.